Multisensory Imagery - Lacey, Simon; Lawson, Rebecca; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Is a pear sweeter than a peach? Which of Mona Lisa$1 (Bs hands is crossed over the other? What would the Moonlight Sonata sound like played by a brass band? Although these are questions that appeal to mental imagery in a variety of sensory modalities, mental imagery research has been dominated by visual imagery. With the emergence of a well-established multisensory research community, however, it is time to look at mental imagery in a wider sensory context. The first part of this book provides overviews of unisensory imagery in each sensory modality, including motor imagery, together with discussions of multisensory and cross-modal interactions, synesthesia, imagery in the blind and following brain damage, and methodological considerations. The second part reviews the application of mental imagery research in a range of settings including individual differences, skilled performance such as sports and surgical training, psychopathology and therapy, through to stroke rehabilitation. This combination of comprehensive coverage of the senses with reviews from both theoretical and applied perspectives not only complements the growing multisensory literature but also responds to recent calls for translational research in the multisensory field.s
Introduction -- Visual Mental Imagery -- Somesthetic Mental Imagery -- Auditory Aspects of Auditory Imagery -- Modulation by Sensory Experience and Comparison to Auditory Mental Imagery -- Motor and Kinesthetic Imagery -- Mental Imagery and Blindness -- Representing 3D Space in Working Memory: Spatial Images from Vision, Hearing, Touch, and Languag -- Crossmodal Mental Imagery -- Is Synesthesia a Form of Mental Imagery? -- Visual Imagery in Haptic Shape Perception -- Auditory Imagery Contains More Than Audition -- Visual and Motor Mental Imagery after Brain Damage -- Imagery Questionnaires: Vividness and Beyond -- Cognitive Neuroscience of Mental Imagery: Methods and Paradigms -- Individual Differences in Object versus Spatial Imagery: From Neural Correlates to Real-World Applications -- Motor and Visual Imagery in Sports -- Mental Imagery and Mental Practice Applications in Surgery: State of the Art and Future Directions -- Mental Imagery and Psychopathology: Examples of Post-Traumatic Stress Disorder and Bipolar Disorder -- Imagery and Cravings -- Clinical Applications of Motor Imagery in Rehabilitation -- Summary and Some Future Directions.
Keywords: Medicine; Neurosciences; Neurology; Consciousness; Biomedicine; Neurosciences; Neurology; Cognitive Psychology